Plant secrets - Goodman, Emily (Charlesbridge, 2008)
Learn the secrets of plant lifecycles, using four common (but very different) plants. Simple text and colorful illustrations show the major phases of plant growth: seed, plant, flower, and fruit. Back matter offers more information on each plant, as well as on each stage of growth.